Sistem Informasi Buku Piket Rumah Dinas Gubernur Provinsi Bengkulu - Zulfiandry, Ricky; Siswanto, Siswanto (UNIVED Press, 2019)
Computer-based information systems have a very important role in providing information systems for every organization or government agency. as is the case at the Official Residence of the Governor of Bengkulu Province. Where currently the picket book is still manual or the data processing process is written one by one on paper and in a ledger. This of course really requires an organized and complex system. And if it is only supported by a manual system, efficiency and effectiveness in presenting this information will not be achieved. The Bengkulu Province Governor's Official House Picket Book Information System is an application that can assist picket officers in processing picket book data which includes recording assets, activities and guests. Apart from that, this application allows for the creation of output reports that will be reported based on day, month and year. The Bengkulu Province Governor's Official Home Picket Book Information System was created using the Visual Basic .Net programming language. Based on the results of the tests carried out, the Bengkulu Province Governor's Official House Picket Book Information System can assist officers in managing data on activities, assets and guests, which up to now has still been done conventionally. And if the officer/admin doesn't have a password, they won't be able to access the Bengkulu Province Governor's Office Picket Book Information System.